2019
DOI: 10.18001/trs.5.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Graphic Warning Label Ratings by Addictions Clients

Abstract: Objectives: Research on sex differences in responses to cigarette graphic warning labels (GWLs) has been limited despite tobacco-related, health disparities for women. We examined whether women had stronger responses to certain labels than to others, whether this pattern differed from men’s, and whether there were overall sex ratings differences. Methods: Smokers (N = 881) in 24, addictions treatment programs rated 3 of 9 Food and Drug Administration-developed labels on credibility, message reactance, quit m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…In this study, we identified that female smokers had over 2.4 folds of smoking cessation intention due to GWLs in comparison with male smokers, which was in line with previous evidences that graphic warning labels were more effective in motivating female smokers to quit [ 32 ]. This might attribute to the fact that women are more sensitive to malignancies and respiratory illnesses depicted on top of the cigarette package, and then induced strong negative emotions [ 4 , 31 , 32 ]. We recommend that sex differences in smoking cessation intention due to GWLs on cigarette packs should be considered when adopting GWLs into tobacco control measures.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, we identified that female smokers had over 2.4 folds of smoking cessation intention due to GWLs in comparison with male smokers, which was in line with previous evidences that graphic warning labels were more effective in motivating female smokers to quit [ 32 ]. This might attribute to the fact that women are more sensitive to malignancies and respiratory illnesses depicted on top of the cigarette package, and then induced strong negative emotions [ 4 , 31 , 32 ]. We recommend that sex differences in smoking cessation intention due to GWLs on cigarette packs should be considered when adopting GWLs into tobacco control measures.…”
Section: Discussionsupporting
confidence: 89%
“…Women have lower rates of successfully quitting, and experience greater risk of certain health consequences of smoking [ 30 ]. Furthermore, women smokers response more strongly to GWLs on cigarette package, and are more likely to consider smoking cessation due to GWLs [ 31 , 32 ]. In this study, we identified that female smokers had over 2.4 folds of smoking cessation intention due to GWLs in comparison with male smokers, which was in line with previous evidences that graphic warning labels were more effective in motivating female smokers to quit [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that gender-targeted and/or gender-tailored tobacco cessation communications have potential to reach this vulnerable group (Campbell et al, 2019;Toll et al, 2008). Visible cessation messages in clinical and population settings may have the potential to motivate women to quit during and even before pregnancy.…”
Section: Study Findings and Discussionmentioning
confidence: 99%
“…Even brief counselling for pregnant women about quitting was found to increase the odds of cessation by 1.7 (Melvin et al, 2000). Studies indicate that graphic warning labels (GWLs) with images of women, babies, and tobacco-related disease were impactful for women from a vulnerable population with high smoking rates (Campbell et al, 2019). Under the NTCP, during efforts to disseminate knowledge and awareness of adverse impact of tobacco use, it was seen that nearly 45.3 per cent of women SLT users did not notice health-related warnings on SLT products, which was more than two times much higher than the male counterparts.…”
Section: Study Findings and Discussionmentioning
confidence: 99%